Women Living with HIV/AIDS and Social Stigma in Semarang - Zulfa Safitri K; Amirudin Amirudin; Ani Margawati (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
The issue of social stigma for PLWHA (People with HIV/AIDS) is still being a serious problem. On the other hand, it contributes to HIV/AIDS cases that have not been detected and have not been gotten special treatment yet. Social stigma, discrimination, exclusion in social life are still being a creepy consequence, especially for women living with HIV Aids. The pressure of social stigma is very influential on the perception of women living with HIV Aids, both married and unmarried to the diseases suffered. This study would like to analyze the perceptions of women living with HIV who face the social stigma that affects health behavior.The method of the study is a qualitative method with the life history approach. The techniques of collecting data are an in-depth interview, participant observation, and literature study. The informants of the study are two women living with HIV Aids already married and unmarried that assisted by Rumah Aira Semarang. The result of the study shows that PLWHA have negative perceptions related to social stigma however they try to resist the stigma so that affecting knowledge and health behavior.